Answer:
[tex]K_E=mgr_E[/tex]
Explanation:
By conservation of energy, the sum of the kinetic and gravitational potential energies at the surface of the Earth must be equal than their sum at infinity, so we have:
[tex]K_E+U_E=K_\infty+U_\infty[/tex]
[tex]\frac{mv_E^2}{2}-\frac{GM_Em}{r_E}=\frac{mv_\infty^2}{2}-\frac{GM_Em}{r_\infty}[/tex]
Where [tex]G=6.67\times10^{-11}Nm^2/kg^2[/tex] is the gravitational constant,[tex]M_E=5.97\times10^{24}kg[/tex] and [tex]r_E=6371000m[/tex] are the mass and radius of the Earth, m is the mass of the particle, [tex]v_E[/tex] its velocity at the surface of the Earth (which would be its escape velocity) and [tex]v_\infty[/tex] and [tex]r_\infty[/tex] are the velocities and distance at infinity, which would be null and infinity respectively, so the right hand side of our equation is 0J, which leaves us with:
[tex]\frac{GM_Em}{r_E}=\frac{mv_E^2}{2}=K_E[/tex]
Also, since the force the molecule experiments is the force of gravity (disregarding drag), we can write its weight in terms of Newton's Law of Gravitation:
[tex]F=mg=\frac{GM_Em}{r_E^2}[/tex]
Which means that:
[tex]\frac{GM_Em}{r_E}=mgr_E[/tex]
So finally putting all together we can write:
[tex]K_E=\frac{GM_Em}{r_E}=mgr_E[/tex]